LEARNING STYLES OF INTROVERT AND EXTROVERT STUDENTS IN THE ENGLISH LEARNING PROCESS - DEWI, KHARISMA YUNITA DEANDRA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Recently, English is the first foreign language taught as a compulsorysubject in Indonesia. We mostly deal with the challenge of learning and using aforeign language, whether at school, at work or in our day-to-day life. This mightbe difficult for Indonesian EFL students to learn. The learners will get thedifficulties when they do not have appropriate learning style in their learningprocess. Therefore, in order to handle the difficulty in their learning, thosestudents must have the learning style applied in learning process. Learning stylesand personality types are closely linked to each other because both of them are thefactors affecting language learning. This study was conducted to investigatelearning style preferred by Introvert and Extrovert students and to examine themost frequently preferred learning style of Introvert and Extrovert students of2012 academic year at English department of Languages and Literature, Facultyof Cultural Studies Universitas Brawijaya in learning process. This study useddescriptive quantitative approach. The participants investigated were 47 studentsof 2012 academic year at English department of Languages and Literatures,Faculty of Cultural Studies Brawijaya University. The data were obtained by thePerceptual Learning Style Preference by Reid and personality type questionnairebased on Myers Briggs theory. The result reveals that kinesthetic and auditory arethe most frequently used learning style of the Introvert students followed bygroup, individual, tactile, and visual while auditory is the most frequently usedlearning style of the Extrovert students followed by group, kinesthetic, tactile,visual, and individual. In conclusion, kinesthetic and auditory are the mostfrequently preferred learning style of Introvert students and auditory is the mostfrequently preferred learning style of Extrovert students. Both groups aresuccessful learners because they have multiple learning styles. The writersuggested that the students should be aware of their learning styles because it isimportant in learning process and career development, for the teacher, they shouldtreat their students well based on their preferred learning styles, and for the otherresearchers the writer also suggested that they can investigate further aboutlearning styles with the other types of the personality. Key words: Learning Style, Introvert and Extrovert, Perceptual Learning StylePreference Questionnaire.